A Study on Metaverse Risks and Risk Perceptions - Sunkyung Shin; Joo-Yeun Park (International Telecommunications Society (ITS), 2024)
The development of Metaverse technology is transforming our lives by shifting our daily activities from the offline to the online world. Metaverse has begun to be recognized as a key industry and future technology by leading the onlineization of daily life that is impossible in reality due to the disaster situation of COVID-19. Metaverse, which is based on the meaning of the expansion and extension of the physical world to the virtual world, is opening a new chapter in human communication and is recognized as a space with new possibilities (Lee et al., 2021). However, the new opportunities and possibilities offered by Metaverse are accompanied by both the positive functions and effects that were expected and targeted in the development and introduction of early metaverse, as well as the unintended negative functions and effects (Dwivedi et al., 2023). In other words, from a future perspective, Metaverse is a revolutionary technology that will change our living environment, and it is quickly permeating our daily lives more than any other technology, but the side effects associated with it are also quickly expanding their influence into our lives. As the industrial importance of the Metaverse has increased, Metaverse technology has been applied to various fields, and new services and platforms based on the Metaverse have emerged, and the number of users has also increased rapidly (Barrera & Shah, 2023). As a result of this situation, the influence of the Metaverse has expanded beyond the industrial dimension to social influence such as individuals and society. In particular, the innovative characteristics of the Metaverse, which are different from existing technologies, have allowed users to experience new side effects that they have never experienced before, and have even expanded to the form of social conflict. These side effects of using the Metaverse are presented as a new challenge and task that must be overcome for the development and future of the Metaverse industry. In response to this situation, this study starts from a critical perspective on the fact that previous studies on Metaverse technology and services have focused too much on the technical aspects and have been discussed only from an optimistic point of view (Bogicevic et al., 2021; Book, 2004; Flavián et al., 2019). In particular, just as all digital media technologies and services have a double-edged sword, the Metaverse also has a double-edged sword, and behind its positive effects lie the risks of negative effects. In this study, we aim to identify and address the risks and threats inherent in Metaverse technologies and services, and to specify and categorize the risks that arise from the use of Metaverse technologies and services, in the context of extending digital risk research and initiating Metaverse risk research. In addition, this study aims to conduct an empirical study on the experiences and perceptions of users who actually use Metaverse technologies and services regarding the risks associated with the use of Metaverse technologies and services. Therefore, this study, considering the situation that instability exists due to the spread and use of the Metaverse, but sufficient discussion has not been made on this, intends to discuss the Metaverse risk from a comprehensive perspective for the stable use and spread of the Metaverse. Starting with this, we aim to establish a theoretical foundation that can continue to expand Metaverse research in the future.
Keywords: 330; Metaverse; Extended reality; Virtual environments; Digital Risk